Dukungan Sosial dan Kepuasan Hidup Mahasiswa: Nongkrong Sebagai Konteks Sosial - Siti Nur Salsabila; Qurrota A'yuni Fitriana (Psychopolytan : Jurnal Psikologi, 2026)
University students experience high levels of academic pressure and consequently require social spaces to fulfill fundamental psychological needs, such as acceptance and connectedness. Leisure socializing (nongkrong) serves not only as a form of recreation but also as a context for fostering emotional bonds and developing social support. Nongkrong can be understood as a form of social leisure freely chosen by participants and providing psychological comfort, in line with Neulinger's Leisure Theory. This study aimed to examine the relationship between social support and life satisfaction among students who routinely engage in nongkrong. A total of 82 students from various universities in Surabaya (60 females, 22 males, mean age 19 years) participated through convenience sampling, with a criterion of gathering at least once a week. Data were collected using the Indonesian-adapted versions of the Satisfaction With Life Scale (SWLS) and the Multidimensional Scale of Perceived Social Support (MSPSS) and analyzed using Spearman correlation. The results showed a significant positive relationship between social support and life satisfaction (ρ = 0.490; p <.001), indicating that higher perceived social support in the context of nongkrong is associated with higher life satisfaction. These findings provide an empirical basis for developing campus well-being programs that consider students’ informal social practices.